2011
DOI: 10.1371/journal.pone.0023888
|View full text |Cite
|
Sign up to set email alerts
|

Stressing the Ubiquitin-Proteasome System without 20S Proteolytic Inhibition Selectively Kills Cervical Cancer Cells

Abstract: Cervical cancer cells exhibit an increased requirement for ubiquitin-dependent protein degradation associated with an elevated metabolic turnover rate, and for specific signaling pathways, notably HPV E6-targeted degradation of p53 and PDZ proteins. Natural compounds with antioxidant properties including flavonoids and triterpenoids hold promise as anticancer agents by interfering with ubiquitin-dependent protein degradation. An increasing body of evidence indicates that their α-β unsaturated carbonyl system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 42 publications
1
49
0
Order By: Relevance
“…The deubiquitinating enzyme inhibitor RA-9 was synthesized and purified as we have previously described (15). The proteasome inhibitor Bortezomib was purchased from Cayman Chemical.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deubiquitinating enzyme inhibitor RA-9 was synthesized and purified as we have previously described (15). The proteasome inhibitor Bortezomib was purchased from Cayman Chemical.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was determined by WST-1 or CellTiter96® AQ ueous One Solution Cell Proliferation assays as previously described (15-17). Briefly, cells were seeded at the concentration of 1,000 or 10,000 per well in 100 μL medium in 96-well plate and treated with the indicated concentrations of drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the E6 oncoprotein targets cellular proteins with PDZ domain, such as p53, to proteasomal degradation via E6 associated protein (E6AP) mediated ubiquitination [16]. These reduced proteins can be rescued by proteasome inhibitors which were also confirmed to execute a selective toxicity against HPV positive cervical cancer cells [17,18]. On the other hand, although sumoylation of HDAC1 protein can strength the stability of it [19], E6 oncoprotein destabilizes HDAC1 protein by reducing the level of the sole sumo conjugation enzyme, Ubc9 [20].…”
Section: Evaluation Of Hypothesismentioning
confidence: 96%
“…Interestingly the specificities of α, β-unsaturated ketone-containing compounds towards various DUBs have been reported to vary considerably. For example whereas b-AP15 was reported to be specific to proteasomal deubiquitinases (D'Arcy et al, 2011), the structurally related compound RA-9 was reported to display more broad range activity and shown to inhibit UCHL1, UCHL3, USP2 and USP8 in addition to the proteasomal DUBs (Anchoori et al, 2011;Coughlin et al, 2014;Issaenko and Amerik, 2012). The chalcone-derivative G5 was also reported to display a broad spectrum of inhibition of DUB activity (Aleo et al, 2006;Nicholson et al, 2008).…”
Section: Proteasomal Dubs As Drug Targets For Cancer Therapymentioning
confidence: 99%